ОСНОВНІ НАПРЯМКИ ТА КРИТЕРІЇ ПІДВИЩЕННЯ ЗАГАЛЬНОЇ ЕФЕКТИВНОСТІ АВТОНОМНОГО ЕЛЕКТРОТРАНСПОРТУ - Шидловський , А.К.; Павлов, В.Б.; Третяк , М.В. (Інститут електродинаміки НАН України, Київ, 2012)
In this paper the main directions and criteria to improve the overall efficiency of autonomous vehicles. It is show that one of the directions of increasing mileage between charges stand-alone electric vehicles and increasing efficiency of its operation is to optimize the efficiency of energy usage with improved management practices power semiconductor converters. References 5.